Self-catalyzed GaAs(P) nanowires and their application for solar cells. (3rd April 2020) - Zhang, Yunyan; Liu, Huiyun
Abstract: Nanowires (NWs) are far superior to traditional thin-film counterparts in making high-efficiency low-cost solar cells (SCs) due to their advanced properties, such as reduced light reflection, strong light trapping, increased defect tolerance, and compatibility with Si substrates. This allows us to greatly reduce the quantity of required material and lessen demands on its quality to achieve sufficient light absorption, leading to substantial cost reduction. Self-catalysed III–V NWs are being widely used for SCs, especially GaAs(P) NWs. However, the special growth mode makes the SC design extremely complex and the existing theories cannot be used directly for guidance. Here, we review the recent breakthroughs and remaining challenges in growing and making self-catalysed NW SCs, with special attention given, but not limited, to GaAs(P) NWs.